Cultural Mismatch in Roma Parents’ Perceptions: The Role of Culture, Language, and Traditional Roma Values in Schools - Lambrev, Veselina (Alberta Journal of Educational Research, 2016)
This article draws on data from a two-year qualitative study exploring the factors contributing to Roma students’ disparate outcomes in Bulgaria. I utilize ethnographic observations, oral history, and in-depth interviews with twenty Roma parents to gain understanding of Roma children’s “cultural capital” and relation to formal schools. The article builds on theoretical orientations, generated primarily in the U.S., that emphasize strengths and the need for culturally relevant pedagogy, and explores the possibility to extend these to the case of Roma communities in Europe. The findings indicate that the traditional education of Roma children differs considerably from the mainstream values emphasized in Bulgarian schools. These include the practice of community-based, informal education, child independence, and early participation in adult life, which have the potential to make the transition from home to school problematic. I argue that if educational equity is the goal, policies and practices must shift their current focus from promoting a monocultural Bulgarian curriculum and pedagogical approaches to meaningful incorporation of culturally relevant content and creating educational environments conductive to Roma students’ learning. Cet article se fonde sur des données provenant d’une étude qualitative qui a duré deux ans et qui a porté sur les facteurs qui contribuent aux résultats divergents des étudiants roms en Bulgarie. Mes données reposent sur des observations ethnographiques, l’histoire orale et des entrevues détaillées auprès de vingt parents roms et ce, pour mieux comprendre le « capital culturel » des enfants roms et leur relation aux écoles formelles. L’article s’appuie sur des orientations théoriques issues surtout de milieux américains et qui soulignent l’importance des bienfaits d’une pédagogie pertinente sur le plan culturel, fait valoir le besoin d’une telle approche et explore la possibilité d’appliquer ces orientations au cas des communautés roms en Europe. Les résultats indiquent que l’éducation traditionnelle des enfants roms diffère considérablement des valeurs communément soulignées dans les écoles bulgares; parmi les éléments divergents, notons la pratique d’une éducation informelle et communautaire, l’autonomie des enfants et la participation précoce à la vie adulte – facteurs qui ont le potentiel de rendre difficile la transition de la maison à l’école. J’affirme que si l’objectif est l’équité en matière d’éducation, les politiques et les pratiques doivent se détourner de la promotion d’un curriculum et d’approches pédagogiques homogènes bulgares vers une intégration significative de contenu culturel pertinent et la création de milieux pédagogiques propices à l’apprentissage par les étudiants roms.